Pendekatan Religius-Rasional Dalam Pendidikan Islam: (Kajian Terhadap Falsafah Dasar Ayat Multikultural al-Baqoroh ayat 62) - Mufidul Abror (Program Studi Pendidikan Agama Islam, 2021)
The reality of the emergence of social conflicts triggered by religious factors leads to grounding Islamic education with a multicultural perspective. Because it's time to review the concept of multiculturalism to manage diversity. The solution steps offered to educational institutions in order to achieve the goals of Islamic education in the context of Indonesia and which will be discussed in this study the author tries to enrich the religious-rational concept in Islamic education through a study of the basic philosophy of multicultural verses. This research uses library research method with descriptive analysis approach. In this study, researchers used data collection techniques by looking for sources from commentaries, books, journals, and articles. The data analysis technique used by the researcher in this research is content analysis, with the assumption that the analysis always displays three conditions, namely objectivity, systematic approach and generalization. The Religious-Rational approach is the foundation and main umbrella for Islamic symbols in education to internalize multicultural values ??in social life with the basic philosophy of Surah al-Baqoroh verse 62 that Islam recognizes the existence of other religions in the world and recognizes the potential for truth that arises from adherents of religions other than Islam.